The effects of a six-week physiotherapist-led exercise and education intervention in patients with osteoarthritis, awaiting an arthroplasty in the South Africa - Saw, Melissa Michelle (Division of Physiotherapy, 2015)
Background: Osteoarthritis (OA) is one of the leading causes of disability worldwide. A major challenge facing those with severe OA is long waiting lists delaying access to joint replacements. Patients are known to wait more than five years for a joint replacement in the Western Cape of South Africa (SA). The main complaint in this population is pain and its consequences including activity limitations, participation restrictions and reduced quality of life. Hip or knee OA is not merely joint degeneration but a condition requiring holistic management, even while waiting for surgery. Most of the literature in this field is available from high income countries exploring the effects of interventions during short waiting periods. Thus research is warranted in a low income country such as SA, in those waiting for long periods to explore the effects of a six-week physiotherapist-led exercise and education intervention. Methods: A single blinded randomised controlled trial, aligned with CONSORT guidelines, was performed at Tygerberg Hospital in the Western Cape, SA. The experimental group attended a six-week group-based physiotherapist-led intervention including education, exercise and relaxation. The control group continued to receive usual care. The primary outcome measure was pain with secondary measures of disability, function, quality of life and self-efficacy. Measures were obtained at six weeks, 12 weeks and six months by a blinded physiotherapist. An open ended questionnaire was completed by the participants in the experimental group at month six. Analysis was by intention to treat. Two-way analysis of variance and post-hoc Tukey comparisons were used for parametric data, Pearson Chi squared calculations for categorical data. Effect sizes were established for significant differences between groups. Results: The study recruited 42 participants from the waiting list for a hip or knee arthroplasty. Mean waiting time was 3.6 ± 2.5 years. Compared to the control group, the experimental group had significant improvements with large effect sizes at month six for pain interference (3.49 ± 2.63 vs. 6.09 ± 2.43; p=0.02, ES=1.15) and function (15m fastest speed walk) (15.09 ± 6.04s vs 20.10 ± 8.79s; p=0.03, ES=0.88). Furthermore, the experimental group displayed significant (p < 0.01) and sustained improvements at month six in pain severity, disability and function (15m normal speed walk, sit-stand, 6-minute walk). Subgroup analysis showed participants with knee OA responded better to the intervention than those with OA of the hip or combined hip and knee OA. Participants enjoyed the intervention reporting improved knowledge, function and activity, pain relief and improvement in psychosocial aspects. Conclusions: A six-week physiotherapist-led exercise and education intervention brought about significant long term improvements in pain interference and functional walking ability in patients with osteoarthritis, awaiting a joint replacement compared with a control group. Such a programme also appears to have significant and sustained improvements in pain severity and disability. Further research with longer follow up is recommended to determine if results are sustained.